The nature and implications of spirit possession among the Tsonga - Shilubane, Paul Xilavi (University of Limpopo, 1990)
Refer to the document
Thesis (M. A. (Anthropology)) -- University of the North, 1990
Keywords: Spirit possession; Tsonga people; Spirit possession; Demoniac possession; Folklore